The Impact of Mobile Assisted Language Learning (MALL) on Student Motivation and Learning Outcomes: Literature Review - Silbila Enova Putri; Putri Ria Fakhrurriana (Universitas Pendidikan Indonesia (UPI), 2024)
Foreign language learning (English) in the digital era is aided by developments in mobile technology. Mobile Assisted Language Learning (MALL) is one of the most rapidly increasing methodologies. The purpose of this study is to look into how MALL affects student motivation and learning results. The literature review was conducted by reviewing various reliable sources such as scientific journals, articles, and research reports. The results show that MALL has a significant positive effect on student motivation and learning outcomes. MALL can increase students' learning motivation through various interactive features, educational games, and easy access to learning materials. In addition, MALL also proved effective in improving students' learning outcomes in vocabulary, grammar, pronunciation, and communication skills. This study concludes that MALL is a useful tool to improve students' motivation and learning outcomes in foreign language learning. Further research is needed to explore the effectiveness of MALLs in various learning contexts and to deploy more innovative and educational MALL software.